2010
DOI: 10.3382/ps.2010-00744
|View full text |Cite
|
Sign up to set email alerts
|

Response to selection for feed conversion ratio in Japanese quail

Abstract: We investigated the effect of selection for 4-wk feed conversion ratio (FCR) on genetic improvement of FCR, BW, weight gain (WG), feed intake (FI), and residual FI (RFI) in Japanese quail. The F line was selected for reduced FCR and the C line was maintained as a randombred control. In each generation, 35 sires and 70 dams were used as parents for the next generation. Three generations of selection were performed. Realized heritability for FCR was calculated as the ratio of cumulative selection response to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 16 publications
3
32
1
2
Order By: Relevance
“…It was stated that progress in FCR also increased body weight. Next, 16.4% increase in body weight at 4 weeks of age reported by researchers (Varkoohi et al, 2010). Similar results were also stated for relative growth rate by Hyánková et al (2001) and those findings are in agreement with our study.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…It was stated that progress in FCR also increased body weight. Next, 16.4% increase in body weight at 4 weeks of age reported by researchers (Varkoohi et al, 2010). Similar results were also stated for relative growth rate by Hyánková et al (2001) and those findings are in agreement with our study.…”
Section: Discussionsupporting
confidence: 93%
“…Varkoohi et al (2010) performed selection in order to amend FCR character and reported selection differential in the first generation 10.22%, selection response 8.21%, heritability as a 0.80. Varkoohi et al (2010) have reported that as a result of selection through the 4 generations, FCR value (2.68) was improved to 2.13. However, selection response and cumulative heritability for mentioned trait decreased.…”
Section: Discussionmentioning
confidence: 99%
“…These estimates were partially higher than previous estimates reported in Japanese quail (Varkoohi et al, 2010); and partially similar to the results obtained by Silva et al (2013) in meat-type quail. However, in the latter, different PL had not been considered for the genetic parameter estimation.…”
Section: Discussioncontrasting
confidence: 56%
“…Quails in the high group of second generation had the highest feed intake (39.2g) and the lowest in low group of first generation (33.1g). Improvement in FCR is due to the population's genetic structure, and to a certain extent, diet and environmental conditions (Varkoohi et al, 2010). Improved FCR for a certain body weight could be partially due to lower maintenance costs and lower fat deposition of birds with higher growth rate (Pym, 1979).…”
Section: Resultsmentioning
confidence: 99%